Dinamika Hubungan Indonesia-Australia: Studi Kasus Kepentingan Australia dalam Konflik Timor Timur - Rumdah; Eko Ribawati (HEURISTIK: Jurnal Pendidikan Sejarah, 2023)
Judging from the historical aspect, Indonesia-Australia relations have a fairly strong amity and enmity side, with a more prominent aspect of enmity. Indonesia's relationship with Australia has had its ups and downs due to notable differences in terms of economic conditions, population, ethnicity, culture and religion. The interests between the two countries also often rub against each other, which also affects the harmony of relations between the two countries. Some cases mainly prevent the two countries from fighting for economic resources. From Operation Seroja onwards, Indonesian military forces were involved in the massacre of East Timorese civilians. The forms of violence committed are very diverse, from forced searches to the number of murder cases to attract international attention. In the 1998 referendum process, Australia was involved as a party involved. Australia in relation to East Timor (post-refrendum East Timor) indirectly applied its hegemony to support Australia's political and economic interests. In the concept of regional security, Australia has a veiled political interest of making East Timor a buffer zone in addition to the economic interests of oil and gas resources in the Timor Pass. The article, written using qualitative methods, aims to provide an overview of the interests of Australia, Indonesia and East Timor in the conflict that occurred in the aftermath of the East Timor inetgration until after the 1998 referendum.